The fundamentals of design management - Best, Kathryn (Lausanne, Switzerland AVA Academia ; La Vergne, TN : Distributed in the USA & Canada by Ingram Publisher Services, 2010)
A guide to managing the people, projects, processes and procedures behind the design of our everyday products, services, environments and experiences. It is suitable for those from various backgrounds such as art and design, business, marketing or media.
How to get the most out of this book. Introduction. Design in context: Design and business cultures; Finance, technology and law; Society, politics and environment; Market demands and user needs; Design audits, briefs and proposals; People; Projects; Products and services. Design overview: The power of design; Design and society; Design projects; The design process; Design skills; Design planning; Project management; Design success. Case study: Legible London: a new way of walking in the UK's capital city. Contextual perspectives: Sorena Veerman; Wen-Long Chen; Dr Miles Park. Management overview: Economics; Business and enterprise; The management process; Business and enterprise planning; Management practice; Business administration; Business success. Case study: MAS Holdings: enterprising ethical retailing. Contextual perspectives: Ruedi Alexander Muller-Beyeler; Joshua L.Cohen; Kevin McCullagh. Accounting and finance: The financial organisation; Financial accounting; Financial reporting; Management accounting; Measuring performance; Measuring value in design. Case study: Phelophepa Healthcare Train: delivering value. Contextual perspectives: Philip Goad; Thomas Lockwood; Krzyzstof Bielski. Marketing and brand communication: Users, customers and markets; Understanding production and consumption; Marketing; Marketing communications; Branding; Brand communications; Vision, values and brands. Case study: Zipcar: the vision driving the world's largest car sharing club. Contextual perspectives: Robert Malcolm; Naoko Iida; Audrey Arbeeny. Design and Innovation: Design, Management and innovation; Design-driven innovation; Brand-driven innovation; Design management for corporations; Design management for small to medium enterprises. Case study: Philips Design: design for a sustainable society. Contextual perspectives: Matt Barthelemy; Sonja Dahl; Simon May. Conclusion. Glossary. Bibliography and resources. Picture credits. Acknowledgements. Working with ethics.
Keywords: Industrial design -- Management